Investigating the molecular and physiological roles of BUD23-dependent protein translation - Voronkov, M (2021)
The human ribosome is extensively modified, containing at least 288 distinct modification sites. Current literature suggests that most ribosomal modifications serve to stabilise the tertiary structure of the ribosome, however this fails to explain why ribosomal RNA (rRNA) modifications tend to cluster in functionally important regions that are vital for translation. Their spatial organisation and high level of conservation throughout all eukaryotes strongly suggest that rRNA modifications are instead responsible for the regulation of ribosomal function. BUD23 is a putative methyltransferase that is responsible for modifying a key residue on the small ribosomal subunit. It also has a second independent function in small ribosomal subunit biogenesis, where its presence is essential for correct ribosomal maturation. While BUD23's role in small ribosomal subunit maturation has been well characterised, studies have failed to determine any functional consequences of its methylation activity. This has led to the idea that the methylation event may be non-essential, or is imparted simply as a quality control marker. Over the course of this project, I aimed to investigate the role of BUD23, with particular focus on the in vivo consequences of its function. By generating two unique mouse models of BUD23, I have established that BUD23 attenuates mitochondrial and metabolic function, and have implicated that this is as a result of its methylation activity. In addition, I have generated a homology model of human BUD23 to explore the mechanisms underlying its core functions, and point to a functional purpose for the existence of the methyl mark on the small ribosomal subunit. Overall, this thesis implicates that BUD23 is responsible for the regulation of tissue and organismal energy balance in a highly selective manner, promoting a selective translational advantage to metabolic transcripts. Its loss has profound implications, resulting in global metabolic defects as a consequence of ribosomal failure.